MILITARY POWER AND MILITARIZATION OF GLOBAL SPACE - Syzov, A.; Koval, O.; Pakholchuk, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The article highlights the concepts of militarization and military power of individual countries by using statistical profiles to compare the Global Firepower Index and Global Militarization Index. The military expenditures of countries with developed economies and developing economies were analyzed. The reasons for the decrease and increase in military expenditures have been established. The indicators of the total military budget, its share of the gross domestic product and the share of global military expenditures were used for the analysis. Key players in the international arena are involved in the comparison, and the main emphasis is on direct and indirect participants in the Russian-Ukrainian war. To compare the military power of countries, data from the military research network was taken. To determine the military burden on the economy, a system of indicators of the global militarization of space was used. The inaccuracy of the indicators was established due to the lack of accurate data on military expenditures, quantitative indicators of armaments, external and internal political dynamics of individual countries. With the help of the available indicators, a comparison of the military power of Ukraine and Russia was derived, and weaknesses in the formation of ratings were identified. Thus, quantitative indicators of human resources, weapons, geography, availability of energy resources are included in the comparison.
Keywords: military expenditures, military power, militarization, military burden, military-economic potential